2006
DOI: 10.1007/s10498-005-4574-2
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Fe2+ and ∑H2S Behavior in Sediments Seasonally Overlain by Hypoxic-to-anoxic Waters as Determined by CSV Microelectrodes

Abstract: Variability of dissolved Fe 2+ and P H 2 S concentrations in porewaters were studied, using cathodic stripping voltammetry (CSV) microelectrodes, in sediments overlain by hypoxic waters in the summer from the southeastern region of Corpus Christi Bay, Texas (CCB) and the Mississippi River Bight (MRB), Louisiana. These measurements were complimented by sediment microcosm studies where oxygen concentrations in the overlying water were manipulated. Sulfate reduction rates, benthic oxygen demand, total reduced sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Experimental studies have shown that cores incubated under hypoxic conditions successively released dissolved manganese (Mn(II)), iron (Fe(II)) and sulfide S(-II)) to the overlying water column. This demonstrates that bottom-water oxygenation impacts the vertical extent of redox zones (Kristiansen et al, 2002;Sell and Morse, 2006).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 84%
See 1 more Smart Citation
“…Experimental studies have shown that cores incubated under hypoxic conditions successively released dissolved manganese (Mn(II)), iron (Fe(II)) and sulfide S(-II)) to the overlying water column. This demonstrates that bottom-water oxygenation impacts the vertical extent of redox zones (Kristiansen et al, 2002;Sell and Morse, 2006).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 84%
“…After closure, oxygen was quickly depleted and sulfide began to accumulate (see above). Also, laboratory experiments using cores sampled in other environments showed a clear relationship between oxygen concentration in the bottom waters and sediment-to-water-column fluxes of Mn(II), Fe(II) and S(-II) (Kristiansen et al, 2002;Sell and Morse, 2006). The kinetics experiment performed by Kristiansen and co-workers clearly showed that reduced compounds accumulated more in the overlying water during more severe hypoxia.…”
Section: Vertical Redox Fluctuations Versus Lateral Heterogeneitymentioning
confidence: 94%
“…However, if the decreasing oxygen trend continues, at some point the sediment will be affected (Kristiansen et al 2002;Sell and Morse 2006).…”
Section: Study Areamentioning
confidence: 99%
“…However, under low oxygen conditions, Shewanella oneidensis was shown to simultaneously reduce Fe(III), NO 3 -and NO 2 -(DiChristina 1992). Fe(II) has also been found under suboxic conditions in sediment porewaters (Sell & Morse 2006) as well as in the oxygen minimum zone in the water column where NO 2 -was also found (Moffett et al 2007). The simultaneous respiration of NO 3 -and O 2 has also been shown to occur within both phytodetritus (Wolgast et al 1998) and coastal sediment (Brandes & Devol 1995).…”
Section: Reducing Processes In Aerobic Environmentsmentioning
confidence: 89%